Assessing the role of texture and mineralogy on organic matter protection and cycling in oxisols - Souza, Ivan Francisco de (2016)
Worldwide, the soil organic carbon (SOC) stock accounts for more C in the form of organic matter (SOM) than the total C in the atmosphere and in the biomass combined. Therefore, in a context of increasing levels of atmospheric CO 2 and its possible impacts on the average global temperature, understanding the factors controlling SOC stocks is key. Despite the large number of factors regulating SOM stocks , managing soil C sequestration is thought to be critical for offsetting the excess of atmospheric CO 2 . Otherwise, soils also could further contribut e to increase the concentration of CO 2 in the atmosphere if faster decomposition rates of SOM is to become an important climate feedback. Up to now, the scientific communit y has not complete answers for these questions. However, important conceptual and technological developments over the last 20 years have boosted our understanding on SOM dynamics. As a result, rather than rel ying on intrinsic resistance of SOM against decomposers, it seems that physical occlusion and chemical reactions within the mineral matrix play a much more significant role on the persistence of reduced C in soils. In addition, these mechanisms can be soil-specific and as such, we addressed the occurrence of these processes in Oxisols. These are the predominant soils in tropical ecosystems and are dominated by low -activit y clays. The specific objectives of this research were to infer (i) the capacit y for SOC storage as a function of soil texture and C -saturation (i.e. lower conversion efficiency of plant litter -C into mineral -organic associations with increasing C additions ; (ii) infer the influence of reactive minerals within the clay+silt fraction of Oxisols on the formation and persist ence of mineral -organic associations in these soils. incorporation of a labeled plant litter (containing mineral-organic associations in Oxisols by We 13 assessed C and performing 15 the N) into incubation experiments conducted throughout 12 months. In the first chapter, we address the incorporation of the 13 C label into mineral -organic associations as related to soil texture and C -saturation. In this chapter, we deomontrate that soil texture has a strong influence on the capacit y for SOC storage and the C -saturation of the fraction <53 m. Additionall y, we observed evidence of higher the contribution of physical protection of SOM within microaggregates pore-space area, with increasing content of the fine fraction . In the second chapter, we address the incorporation of the labeled plant litter ( 1 3 C and 15 N) into mineral-organic associations as affected by the mineralogy of the mineral mat rix. In this chapter, we demonstrate that amorphous Al -/Fe- (hydr)oxides are the main components within the fine fraction of Oxisols involved in the formation and the persistence of SOM. Given the relativel y low concentration of amorphous Al -/Fe-(hydr)oxides within the fine fraction and their contribution for the protection of SOM , suggests that SOC stocks in the tropics could be very sensitive to environmental changes. Therefore, further resear ch on this subject would evaluate the composition of mineral -organic associations in tropical soils. This would help to predict the possible impacts of climate change on SOM cycling in tropical ecosystems. In the third chapter, we used scanning transmission electron microscopy (STEM) and thermal anal ysis to probe the c hemical composition of mineral -organic associations in a C-rich Oxisol (not included in the incubation experiment). In this chapter, we used elemental mapping to demonstrate that SOM is closel y associated to Al-/Fe-(hydr)oxides. Furthermore, we submitted t he sample to thermal anal ysis to relate mineral dehydroxylation to the oxidation of SOM. Indeed, we observed strong oxidation reactions to overlap with dehydrox ylation of gibbsite, short -range order Al species and goethite. Our results contribute to improv e the current understanding on the minerals and the mechanisms by which these components interact and ultimatel y protect SOM against decomposition in Oxisols.